Antioxidant activity of rat liver with a low resistance to hypoxia after systemic ischemia reperfusion - Gulnar A. Bayburina; Elena A. Nurgaleeva; Ajgul F. Samigullina; Ekaterina R. Farshatova; Timur I. Ganeev; Eduard F. Agletdinov; Tatyana V. Tarasova (Russian Open Medical Journal)
Objective — To assess the antioxidant activity of rat liver after systemic ischemia reperfusion (IRP). Material and Methods — The study was conducted on 70 male rats. For all animals of the treatment group (n=35) under ether anesthesia, we were stopping stopping systemic circulation for five minutes. After that, the animals were given an external cardiac massage and artificial lung ventilation. We did not perform circulatory arrest after ether anesthesia in animals of the control group (n=35). In all animals, we were measuring the levels of serum hormones (corticosterone, aldosterone), the content of glucocorticoid and mineralocorticoid receptors in liver homogenates, and the activity of enzymes of the antioxidant system (superoxide dismutase and catalase). We were making control measurements on days 1, 3, 5, 7, 14, 21, and 35 after the simulated IRP. Results — On day 1 after simulation of IRP development, the levels of cortisol and aldosterone in the serum of treatment group rats were significantly higher, by 14.3% and 33.5%, respectively, compared with the control group. In response to stress (IRP), we observed the highest concentration of cortisol in the blood of treatment group rats on day 3 (p=0.0002), which decreased afterwards. On day 1 after IRP, there was a reduction in the activity of superoxide dismutase and catalase in treatment group rats, by 50.3% and by 29%, respectively (p<0.0001). The lowest antioxidant activity in the rat liver after IRP was observed on days 3-7. Conclusion — Systemic IRP is associated with pronounced changes in the dynamics of corticosteroid receptors in the liver, which leads to a reduction in the activity of key antioxidant enzymes.